Comparative developmental analysis of Drosophila and Tribolium reveals conserved and diverged roles of abrupt in insect wing evolution. - Ravisankar, P.; Lai, Y.T.; Sambrani, N.; Tomoyasu, Y. (Developmental Biology, 2016)
Morphological innovation is a fundamental process in evolution, yet its molecular basis is still elusive. Acquisition of elytra, highly modified beetle forewings, is an important innovation that has driven the successful radiation of beetles. Our RNAi screening for candidate genes has identified abrupt (ab) as a potential key player in elytron evolution. In this study, we performed a series of RNA interference (RNAi) experiments in both Tribolium and Drosophila to understand the contributions of ab to the evolution of beetle elytra. We found that (i) ab is essential for proper wing vein patterning both in Tribolium and Drosophila, (ii) ab has gained a novel function in determining the unique elytron shape in the beetle lineage, (iii) unlike Hippo and Insulin, other shape determining pathways, the shape determining function of ab is specific to the elytron and not required in the hindwing, (iv) ab has a previously undescribed role in the Notch signal-associated wing formation processes, which appears to be conserved between beetles and flies. These data suggest that ab has gained a new function during elytron evolution in beetles without compromising the conserved wing-related functions. Gaining a new function without losing evolutionarily conserved functions may be a key theme in the evolution of morphologically novel structures.